Micro Stirling Engine Controlled by Light - S. Pipatsart; S. Kamoldilok; P.P. Yupapin (My University, 2011)
This paper proposes a new technique for a micro Stirling engine operation using leaky light resonant or whispering gallery modes (WGMs) in a nano-waveguide, in which the nano-waveguide is designed and configured by a nanoring resonator. By using the Optiwave programming based on Finite Difference Time-Domain (FDTD) method, an InGaAsP/InP nanoring resonator was designed and simulated. The simulation results obtained have shown that the leaky light resonant modes can be controlled by the ring radius variations, whereas the maximum resonant peak of nanoring resonator is occurred at the inner and outer ring radii of 0.775 and 1.55 μm respectively. The maximum peak intensity of the nanoring resonator is 12000 W/m2. Finally, the use of leaky light mode resonant peak of the center nanoring resonator for micro-Stirling engine is discussed in details.
Keywords: Nanoring; Waveguide; Photonic and Optical Devices